2017
DOI: 10.1089/hgtb.2016.185
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Identification and Quantification of DNA Species by Next-Generation Sequencing in Adeno-Associated Viral Vectors Produced in Insect Cells

Abstract: Recombinant adeno-associated viral (rAAV) vectors have proven excellent tools for the treatment of many genetic diseases and other complex diseases. However, the illegitimate encapsidation of DNA contaminants within viral particles constitutes a major safety concern for rAAV-based therapies. Moreover, the development of rAAV vectors for early-phase clinical trials has revealed the limited accuracy of the analytical tools used to characterize these new and complex drugs. Although most published data concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…The percentages of DNA contaminants were published in Lecomte et al., 64 Ye et al., 67 and Penaud-Budloo et al. 68 …”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations
“…The percentages of DNA contaminants were published in Lecomte et al., 64 Ye et al., 67 and Penaud-Budloo et al. 68 …”
Section: Main Textmentioning
confidence: 99%
“… 67 Moreover, less than 0.04% of rep and cap sequences contaminated the rAAV1, rAAV2, and rAAV8 vectors produced in the OneBac2.0 cell line by baculovirus infection. 23 Finally, we recently published that less than 0.1% of Illumina reads corresponded to rep-cap genes in rAAV8 batches produced in the dual-baculovirus/Sf9 cells system 68 ( Table 3 ).…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…rAAV vectors were produced and purified based on previous studies in adherent HEK293 13,14 or Sf9 cells 15 and finally buffered in 1Â PBS (phosphate buffered solution). Empty and full particles from some AAV vectors were purified by 2 rounds of cesium chloride gradients as described previously in Ayuso et al 16 When indicated, AAV vectors produced in HEK293 cells were purified by tangential flow filtration (TFF) using a 300 kDa modified polyester membrane from Repligen (Waltham, MA) and buffered in 1Â PBS (10 mM Na 2 PO 4 , 1.8 mM KH 2 PO 4 , 4.27 mM KCl, and 137 mM NaCl, pH 7.4).…”
Section: Aav Production and Purificationmentioning
confidence: 99%